THE BURMESE CINNAMOMUM (LAURACEAE)*) - KOSTERMANS, A.J.G.H. (Research Center for Biology, 1998)
Â The Burmese species of Cinnamomutn are revised and 11 speciesare recognized. Out of these eight new species are described for the first time.